Cluster of Sports Ecological Tourism - Anatoly Yakovlevich Zaporozhan (Управленческое консультирование)
The article is devoted sports eco-tourism in the Russian, which includes the active forms of rec-reation and sports trips including pedestrian , water , skiing. Trere are unique natural features for the development of eco-tourism sports in Russia. The initial task of the sports ecological tourism, is that it should be organized. It is not economically profitable to engage in sports eco-tourism for big business, so small business should organize this process. However, there are serious problems in its organization that small businesses do not manage them selves. At the same time, the development of eco-tourism sports is necessary for states of the Russian Federation. Therefore it is necessary to unite small business with states of the Russian Federation in the form of the cluster of sports federations of ecological tourism